Biomolecules as Model Indicators of In Vitro and In Vivo Cold Plasma Safety - Heslin, Caitlin; Boehm, Daniela; Gilmore, Brendan F.; Megaw, Julianne; Freeman, Theresa A.; Hickok, Noreen J.; Cullen, P. J.; Bourke, Paula (Frontiers in Physics, 2021)
The potential applications for cold plasma in medicine are extensive, from microbial inactivation and induction of apoptosis in cancer cells to stimulating wound healing and enhancing the blood coagulation cascade. The safe bio-medical application of cold plasma and subsequent effect on complex biological pathways requires precision and a distinct understanding of how physiological redox chemistry is manipulated. Chemical modification of biomolecules such as carbohydrates, proteins, and lipids treated with cold plasma have been characterized, however, the context of how alterations of these molecules effect cell behaviour or in vivo functionality has not been determined. Thus, this study examines the cytotoxic and mutagenic effects of plasma-treated molecules in vitro using CHO-K1 cells and in vivo in Galleria mellonella larvae. Specifically, albumin, glucose, cholesterol, and arachidonic acid were chosen as representative biomolecules, with established involvement in diverse bioprocesses including; cellular respiration, intracellular transport, cell signalling or membrane structure. Long- and short-term effects depended strongly on the molecule type and the treatment milieu indicating the impact of chemical and physical modifications on downstream biological pathways. Importantly, absence of short-term toxicity did not always correlate with absence of longer-term effects, indicating the need to comprehensively assess ongoing effects for diverse biological applications.